AB0536 Immunosuppressive Therapy is Promising for Pulmonary Arterial Hypertension Associated with Connective Tissue Disease (CTD-PAH). (9th June 2015) - Takeshima, Y.; Iwasaki, Y.; Kato, R.; Sumitomo, S.; Shirai, H.; Natsumoto, B.; Ota, M.; Teruya, S.; Tsuchiya, H.; Komai, T.; Hanata, N.; Shoda, H.; et al.
Abstract : Background: Association of CTD is one of the poor prognostic factors for PAH patients. Although it remains unclear whether immunosuppressive therapy is effective for CTD-PAH, the efficacy of immunosuppressive agents for CTD-PAH has been reported recently. PAH patients with systemic lupus erythematosus (SLE) or mixed connective tissue disease (MCTD), especially in early stage, are suggested to be good responders to immunosuppressive therapy [1]. Objectives: To evaluate the efficacy of immunosuppressive therapy for CTD-PAH (except SSc-PAH) patients by close monitoring with right heart catheterization (RHC). Methods: Here we report clinical courses of 6 CTD-PAH cases under management with immunosuppressive agents. In all cases, we started high-dose prednisolone (PSL) followed by intravenous cyclophosphamide (IVCY) without adding or modifying vasodilators and evaluated therapeutic efficacy on hemodynamics with RHC. Initial post-therapeutic RHC was performed within three months. Paired t-test was used for comparison of pre- and post-therapeutic hemodynamics: mean pulmonary arterial pressure (mPAP) and pulmonary vascular resistance (PVR). In one case, we analyzed her peripheral blood by Fluorescence Activated Cell Sorting (FACS) analysis before and after IVCY therapy. Results: All cases were Japanese females and mean age was 41.3±12.2 years old; one with SLE, one with SLE plus CREST syndrome, one with MCTD and three with Sjögren syndrome. Each hemodynamic was significantly improved. Mean mPAP was 41.0±9.5 mmHg and 27.0±8.5 mmHg ( p <0.01), and mean PVR was 7.89±3.45 WU and 5.14±2.12 WU ( p <0.05) in pre- and initial post-therapeutic RHC respectively. After first follow-up RHC, vasodilator therapy was modified if necessary. In four cases, the second RHC was performed within half a year after the first evaluation. Although mPAP got slightly worse (31.8±5.9 mmHg), PVR maintained improvement (5.28±1.34 WU). The analysis of B-cell count showed reduction from 241 /μL to 129 /μL. Conclusions: High-dose PSL and IVCY are effective to all cases, indicating the importance of the immune system in CTD-PAH etiology. RHC revealed that only high-dose PSL can remarkably reduce mPAP and PVR. The response to preceding PSL monotherapy could predict overall effectiveness of immunosuppressive therapy for CTD-PAH patients. In addition, B-cell reduction in PBMC was apparent after IVCY, suggesting that B-cell count may predict activity. References: Jais X et al. Arthritis Rheum. 2008;58:521-31. Disclosure of Interest: None declared